2010
DOI: 10.1680/wama.900063
|View full text |Cite
|
Sign up to set email alerts
|

The role of trunk mains in discolouration

Abstract: Understanding and managing the causes of drinking water discolouration are key challenges for the worldwide water industry. Discolouration is a major cause of customer contacts, undermining consumer confidence. Despite significant investment in the UK in the last 15 years in replacing/lining cast iron pipes and improving water treatment processes, discolouration continues to be an issue. Evidence is presented suggesting that trunk mains, which have largely been ignored in terms of rehabilitation and maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…When clustering the contacts temporally, it was opted to do this as one group across the three DMAs. The DMAs were interconnected and served by one water source and studies have shown that over 40% of CCs are explained by clusters affecting multiple DMAs (Husband et al, 2010). The total individual customer contacts in the three DMAs for the one year period was 223.…”
Section: Results Of Transferability To Full Evaluationmentioning
confidence: 99%
“…When clustering the contacts temporally, it was opted to do this as one group across the three DMAs. The DMAs were interconnected and served by one water source and studies have shown that over 40% of CCs are explained by clusters affecting multiple DMAs (Husband et al, 2010). The total individual customer contacts in the three DMAs for the one year period was 223.…”
Section: Results Of Transferability To Full Evaluationmentioning
confidence: 99%
“…& Water quality sampling data linked to DMA & Water chemistry data for Service Reservoirs (SRVs) and Water Treatment Works (WTW) & Water supply system connectivity such as which WTWs supply which WQZ (and hence DMA) and which SRVs supply which DMAs & DMA information: % of certain types of pipe material calculated from overall pipe lengths & Clusters of customer contacts: individual customer contacts are rarely indicative of a widescale water quality problem, but multiple contacts within a short time window could be (Husband et al 2010). The Density-Based Spatial Clustering of Applications with Noise (DBSCAN) algorithm was used in MATLAB to identify temporal clusters of contacts (Ester et al 1996).…”
Section: Data Analysis and Pre-processingmentioning
confidence: 99%
“…While the hydraulic mobilisation of iron and manganese deposits has been long known to result in discoloured water, the presence of discoloured water can also be due to other processes such as biofilm mobilisation or chemical interactions between pipe materials and water acidity [7][8][9][10][11]. Discolouration has been shown to significantly vary even between different parts of the same water distribution network and yet is still similarly experienced throughout different countries regardless of widely-varying factors between their Water Distribution Systems (WDS) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Once a sufficient number of discolouration complaints have been reported in the area, the company may decide to reline (or replace) old mains believed to be the cause of significant discolouration [6,11], particularly if this is going to help address additional issues (e.g., leakage). However, cleaning and especially rehabilitating WDS mains is expensive and can still potentially only have limited effect if the discolouration material was mobilised from a different section of the network [15].…”
Section: Introductionmentioning
confidence: 99%